Couples’ socioeconomic resources and completed fertility in Poland - Osiewalska, Beata (Studia Demograficzne, 2015)
Recently, a growing number of studies have examined the impact of educational level and educational enrolment on the childbearing behaviour of both sexes. At the same time, other socioeconomic characteristics, such as educational field or occupation, are usually neglected or, if included, focus only on women. This study aims at analyzing how socioeconomic resources of both partners in a couple affect their completed fertility in a relatively gender-conservative country – Poland. As a representative of the postsocialist European countries, Poland is an interesting case study, in which women are often double burdened and the conditions to develop a family are more difficult. Since behavioural drivers could differ between parents and childless couples, the Bayesian Zero-Inflated Poisson model consisting of two states (childlessness and parenthood) is applied. The first-wave Generations and Gender Survey (GGS) data for Poland from 2011 are used. The results confirm that including both partners’ socioeconomic resources in the model increases the ability to characterise couples’ childbearing behaviour. In particular, the occupation of both partners occurs to have a substantial influence on their completed family size.